Metaplastic carcinoma of the breast containing three histological components: a case report - Liu, Huan; Zhao, Gang; Fan, Zhimin; Wu, Di; Qu, Fengjiang (Frontiers in Oncology, 2024)
Malignant breast tumors mainly arise from the ductal and lobular epithelium, whereas sarcomas, which originate from the stromal tissues of the breast, account for less than 5% of cases. Mostly, these tumors consist of a single tissue type, rendering malignant breast tumors with three distinct tissue types exceedingly rare. We report a unique case of a malignant breast tumor comprising three tissue types: squamous cell carcinoma (approximately 25%), invasive ductal carcinoma (approximately 5%), and fibrosarcoma (approximately 70%). Given the case’s rarity, pre-operative imaging and tumor biopsy failed to yield definitive diagnostic information, we detail the patient’s clinical and therapeutic process, providing insights for physicians on clinical diagnosis and treatment.